2014
DOI: 10.1177/0886260514539847
|View full text |Cite
|
Sign up to set email alerts
|

Athletic Coaches as Violence Prevention Advocates

Abstract: Adolescent relationship abuse (ARA) is a significant public health problem. Coaching Boys Into Men (CBIM) is an evidence-based ARA prevention program that trains coaches to deliver violence prevention messages to male athletes. Assessing acceptability and impact of CBIM on coaches may inform prevention efforts that involve these important adults in health promotion among youth. As part of a two-armed cluster-randomized controlled trial of CBIM in 16 high schools in Northern California, coaches completed baseli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 33 publications
0
25
0
Order By: Relevance
“…Fonagy et al's (2009) work on anti-bullying programs in elementary schools found that successful interventions have a whole-school approach, involving administration and training for teachers. In a study by Jaime et al (2014), the authors found that high school athletic coaches who participated in bystander education training were more likely to intervene themselves, as well as discuss bystander intervention with their teams and encourage pro-social action. Thornberg et al's (2012) qualitative study with adolescents also found that students identified coaches as motivating them to step in as bystanders in bullying situations.…”
Section: Pro-social Modelingmentioning
confidence: 99%
See 1 more Smart Citation
“…Fonagy et al's (2009) work on anti-bullying programs in elementary schools found that successful interventions have a whole-school approach, involving administration and training for teachers. In a study by Jaime et al (2014), the authors found that high school athletic coaches who participated in bystander education training were more likely to intervene themselves, as well as discuss bystander intervention with their teams and encourage pro-social action. Thornberg et al's (2012) qualitative study with adolescents also found that students identified coaches as motivating them to step in as bystanders in bullying situations.…”
Section: Pro-social Modelingmentioning
confidence: 99%
“…Research would also be useful to evaluate whether explicit training for campus community leaders (i.e. Residence Life Staff, coaches) may result in a greater ability to model and assist students with pro-social interventions (Jaime et al 2014).…”
Section: Pro-social Modeling: Research Directions For College Campusesmentioning
confidence: 99%
“…Coaches have been identified as important source of messaging for studentathletes about what constitutes appropriate and inappropriate off-field behavior (Jaime et al, 2014). No research to date has assessed whether coach expectations about appropriate off-field conduct and team consequences for violating those expectations are related to the likelihood team members will intervene to prevent inappropriate sexual behavior.…”
mentioning
confidence: 99%
“…In underserved settings, interpersonal relationships within non-familial adults (such as coaches) are important (Levine & Munsch, 2016). The coach-athlete relationship is essential because coaches have the ability to become role models and mentors to their athletes due to the consistency and time spent in games, practices, and off-court activities (Jaime et al, 2015). Furthermore, research shows that athletes' perceptions of strong coach-athlete relationships are linked to positive developmental experiences (Jowett, 2008).…”
Section: The Coach's Role In Inner-city Underserved Settingsmentioning
confidence: 99%
“…In sport, coaches consistently spend time and interact with their athletes throughout the season, whether it is during practice, games or tournaments. Coaches can become role models (Jaime et al, 2015) and develop a close, natural mentoring relationship with athletes (DuBois & Silverthorn, 2005). Research shows that natural mentoring relationships that occur over years have the strongest effects in youth (DuBois & Silverthorn).…”
Section: Mentorshipmentioning
confidence: 99%